Effects of Yoga Interventions on Sleep Quality Among Adult Women with Sleep Problems: A Systematic Review - I Gede Yogi Lingga Pradipa; Nyoman Intan Permatahati Wiguna; I Made Bagus Krishna Wiguna; Riska Ramadona. H; Sarah Angie Sihotang; I Putu Esa Ika Putra Juni Artana (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Introduction: Sleep problems are common health complaints and occur more frequently in adult women than in men. These disturbances are influenced by biological and psychosocial factors and negatively affect quality of life and overall health. Yoga has emerged as a non-pharmacological approach for managing sleep problems. This systematic review aimed to evaluate the effectiveness of yoga in improving sleep quality and reducing insomnia in severity among adult women. Method: This study was conducted as a systematic literature review following PRISMA guidelines. Literature searches were performed in PubMed, Cochrane Library, and ScienceDirect. Included studies consisted of controlled clinical trials to assessing yoga interventions in adult women with sleep problems. Data were extracted and synthesized narratively. Discussion: The reviewed studies generally reported improvements in subjective sleep quality following yoga interventions particularly among women with poor baseline sleep quality. In contrast findings related to objective sleep parameters were inconsistent. Differences in yoga styles, intervention, duration, and study populations contributed to variability in outcomes. Conclusion: Yoga may serve as a safe and feasible non-pharmacological intervention to improve subjective sleep quality in adult women. Further high-quality studies with standardized protocols and objective sleep assessments are required to strengthen the evidence.